Perencanaan Jembatan Desa Langon Kecamatan Tahunan Kabupaten Jepara - Indra Firmansyah; Akhmad Wahyu Nur Ikhsan; Bahril Aziq; Nurfatkhan Hamzah Firmana; Sutrisno Sutrisno (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Bridge planning is a fundamental aspect in the development of transportation infrastructure that functions to connect regions, facilitate traffic flow, and support economic and social growth in the community. This study aims to comprehensively examine the stages of bridge planning, from identifying traffic needs and analyzing geotechnical conditions to selecting a structure type, and evaluating technical, economic, and environmental aspects. The methods used include field surveys, traffic data collection, design load analysis, and structural simulation using modeling software. The study results indicate that bridge type selection is not only determined by load capacity and cost efficiency, but must also consider sustainability, aesthetics, and the impact on the surrounding ecosystem. This study emphasizes the importance of integrating technical, social, and environmental aspects in bridge planning, so that the resulting design can provide a safe, efficient, and sustainable solution. Thus, bridge planning is not merely a technical process, but also a development strategy that supports connectivity and community welfare.